The Misdiagnosis and Consequences of the Odontogenic Orocutaneous Fistula by Medical Doctors: A Case Report - Nihal Altunok Ünlü (Galenos Yayinevi, 2021)
It is possible to describe the term fistula as an abnormal connection between different parts of the body. Untreated, specific infections or diseases, chronic infections, congenital deformities, traumatic injuries and postoperative recovery abnormalities may lead to the formation of fistulas. The most common types of oral fistulas can be classified as dentoalveolar, oroantral, oronasal, and orocutaneous fistulas.Dentists and doctors can frequently misdiagnose odontogenic cutaneous fistulas as cutaneous lesions or non-odontogenic infections. As a consequence of an incorrect diagnosis, it is possible for patients to undergo unneeded and ineffective treatments, such as the surgical excision of the cutaneous lesion, multiple biopsies, and repeated antibiotic administration. It has been observed that misevaluation of the lesion and repeated ineffective interventions can lead to scar formation on the skin, pit defects, hyperpigmentation, and iatrophobia.In this case report, we aimed to present the follow-up results of a patient with an odontogenic orocutaneous fistula who was misdiagnosed and treated by medical doctors from different branches.